First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Integrative phylogenetic, phylogeographic and morphological characterisation of the Unio crassus species complex reveals cryptic diversity with important conservation implications - M. Lopes-Lima; J. Geist; S. Egg; L. Beran; A. Bikashvili; B. Van Bocxlaer; A.E. Bogan; I.N. Bolotov; O.A. Chelpanovskaya; K. Douda; V. Fernandes; A. Gomes-dos-Santos; et al. (Molecular Phylogenetics and Evolution, 2024)

Exploring the Ecology of Deep-Sea Hydrothermal Vents in a Metacommunity Framework - Lauren S. Mullineaux; Anna Metaxas; Stace E. Beaulieu; Monika Bright; Sabine Gollner; Benjamin M. Grupe; Santiago Herrera; Julie B. Kellner; Lisa A. Levin; Satoshi Mitarai; Michael G. Neubert; Andreas M. Thurnherr; et al. (Frontiers in Marine Science, 2018)

Epidemiology and potential associated risk factors of drug-related problems in hospitalised children in the United Kingdom and Saudi Arabia - Asia N. Rashed; Antje Neubert; Stephen Tomlin; John Jackman; Hani Alhamdan; Adnan AlShaikh; Ahmed Attar; Mohammed Aseeri; Lynda Wilton; Ian C. K. Wong (European Journal of Clinical Pharmacology, 2012)

Risk factors associated with adverse drug reactions in hospitalised children: international multicentre study - Asia N. Rashed; Ian C. K. Wong; Noel Cranswick; Stephen Tomlin; Wolfgang Rascher; Antje Neubert (European Journal of Clinical Pharmacology, 2012)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Women encounter ADRs more often than do men - Y. Zopf; C. Rabe; A. Neubert; K. G. Gaßmann; W. Rascher; E. G. Hahn; K. Brune; H. Dormann (European Journal of Clinical Pharmacology, 2008)

Ectomycorrhiza communities of red oak (Quercus rubra L.) of different age in the Lusatian lignite mining district, East Germany - S. Gebhardt; K. Neubert; J. Wöllecke; B. Münzenberger; R. F. Hüttl (Mycorrhiza, 2007)

What can we learn about the lipid vesicle structure from the small-angle neutron scattering experiment? - M. A. Kiselev; E. V. Zemlyanaya; V. K. Aswal; R. H. H. Neubert (European Biophysics Journal, 2006)

Characterization of Mixtures of Alkyl Polyglycosides (Plantacare) by Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry - Andrea V. Khn; Reinhard H. H. Neubert (Pharmaceutical Research, 2004)